2018 IEEE International Conference on Robotics and Automation (ICRA) 2018
DOI: 10.1109/icra.2018.8461107
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Adaptation in an Energy Efficient Vibration-Based Robot

Abstract: Morphological computation is a concept relevant to robots made of soft and elastic materials. It states that robot's rich dynamics can be exploited to generate desirable behaviors, which can be altered when their morphology is adapted accordingly. This paper presents a low-cost robot made of elastic curved beam driven by a motor, with morphological computation and adaptation ability. Simply by changing robot's shape and the rotating frequency of the motor that vibrates the robot's body, the robot is able to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While in this work we choose a wooden surface where the effect of different resonance frequencies has been shown to be significant (Nurzaman et al, 2015; Reis et al, 2013; Reis & Iida, 2013), which showed some initial works that discuss the importance of morphology and energy efficiency, it is interesting to perform experiments in other types of surfaces as a future work. There are several papers which relate optimum energy with resonance frequency (Katiyar et al, 2018); however, it is not the scope of this article. The main goal of this article is to explain and demonstrate that adaptive behavior can be achieved in a more power-efficient manner through the use of a shape-changing elastic body.…”
Section: Discussionmentioning
confidence: 99%
“…While in this work we choose a wooden surface where the effect of different resonance frequencies has been shown to be significant (Nurzaman et al, 2015; Reis et al, 2013; Reis & Iida, 2013), which showed some initial works that discuss the importance of morphology and energy efficiency, it is interesting to perform experiments in other types of surfaces as a future work. There are several papers which relate optimum energy with resonance frequency (Katiyar et al, 2018); however, it is not the scope of this article. The main goal of this article is to explain and demonstrate that adaptive behavior can be achieved in a more power-efficient manner through the use of a shape-changing elastic body.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, researchers have widely expanded on another robotics field in recent years: soft robotics. Soft robotics, which generally refer to robotic systems made at least partially out of soft materials, have seen growing adoption due to their compliant and shape-adaptive nature, low implementation costs, and energy efficiency (Nurzaman, Iida, Margheri, & Laschi, 2014;Wang, Nurzaman, & Iida, 2017;Katiyar, Kandasamy, Kulatunga, Mustafizur, Iida, & Nurzaman, 2018;Laschi, Mazzolai, & Cianchetti, 2016). In lieu of the barriers that we mention above, soft grippers could represent a solution for improving mobile manipulator-based social service robots due to their adaptability in grasping myriad household objects (Shintake, Cacuciolo, Floreano, & Shea, 2018).…”
Section: Roboticsmentioning
confidence: 99%
“…Piezoelectric soft robots [12,13] accomplish rapid galumphing (≈200 Hz) but suffer from motion instability owing to their flexible structures. Conversely, hopping robots, [14][15][16] actuated by servomotors, can achieve stable and efficient galumphing at lower frequencies (<50 Hz). Nonetheless, prior implementations situated the actuator on the vertical plane, necessitating an additional module for horizontal steering.…”
Section: Introductionmentioning
confidence: 99%